Administration of Proton Pump Inhibitors with and without Inulin and its Effect on Kidney Function: An Experimental Study on Rabbit Model - Sana Masood, Naveed Ahsan, Aqsa Muhammad Saleem, Fiza Soomro, Sarwat Jahan, Ghulam Serwar Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the effect of various PPIs (Omeprazole Esomeprazole & Pantoprazole) with and without Inulin on renal functions and serum electrolytes in the rabbit model. Study Design: An experimental study was conducted by the Department of Pharmacology and Therapeutics, Liaquat University of Medical & Health Sciences, Jamshoro, Sindh. Place and Duration: This study was completed in a duration of 6 months from 1st February 2021 to 31st July 2021. Methodology: Male and female rabbits weighting 1 to 3 Kilograms apparently healthy with no known illness were selected for the sample. In total 56 rabbits matching study eligibility criteria were included in the study and randomly divided into seven study groups each comprising of eight rabbits. Three groups were provided with three different PPIs i.e. Omeprazole, Esomeprazole and Pantoprazole while other three groups were provided with three different PPIs as well as inulin. However, the control group was only provided with placebo. Blood samples were collected at day 0 and at the end of 6th week. Serum electrolytes were analyzed for serum Magnesium, Calcium, Urea and Creatinine by using Cobas C-311 analyzer. Data was analyzed using SPSS version 19. Results: The study found no statistically significant differences in pre and post-intervention weight of rabbit in any of the experimental groups. The serum urea and creatinine levels showed considerable rise following intake of PPI, indicating a somewhat diminished efficiency of the kidneys to get rid of the body from excess urea and creatinine. However, the rise in urea and creatinine was statistically significant for Group A and Group C with rise in creatinine level following use of Omeprazole and Pantoprazole respectively (p-value <0.05).Electrolyte deficiencies were observed among all experimental groups. Groups that were treated with PPIs and inulin both showed much improved results as compared to rabbits which were treated with PPIs only. Practical Implications: Administration of PPIs along with inulin among human subjects to reduce the adverse effects; specially among critically ill patients or patients with compromised renal function human subject evidence needs to be established by conducting similar trials. This can be breakthrough in treatment protocols for gastritis and patients with renal disease who are also need to take PPIs for any medical indication. Conclusion: Proton Pump Inhibitors significantly change the normal electrolyte composition by increasing concentration of Serum Urea & Creatinine. However simultaneous inulin administration prevent most imbalances and possibly serves to reduce the adverse events associated with use of PPIs significantly. Keywords: Proton Pump Inhibitors, Inulin, Electrolytes,